2009
DOI: 10.1183/09031936.00075309
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse alveolar haemorrhage: factors associated with in-hospital and long-term mortality

Abstract: Diffuse alveolar haemorrhage (DAH) is a feature of several immune and nonimmune disorders. Reported prognosis is poor, with in-hospital mortality ranging from 20% to 100%. Early identification of prognostic factors may be useful in the initiation of appropriate treatment.We retrospectively analysed the charts of all patients referred to a university hospital for DAH between 1980 and 2008. Variables associated with in-hospital and long-term mortality were determined using a logistic regression model and the Kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 46 publications
5
68
0
6
Order By: Relevance
“…Some lessons can be learned from our case. First, prompt diagnosis and adequate treatment are crucial factors for the prognosis of life-threatening DAH, as early diagnosis and immediate therapeutic intervention by steroid were instrumental in helping our patient survive DAH [14,15]. Second, clinicians should be alert to the possibility that DAH can occur in patients taking methimazole.…”
Section: Discussionmentioning
confidence: 98%
“…Some lessons can be learned from our case. First, prompt diagnosis and adequate treatment are crucial factors for the prognosis of life-threatening DAH, as early diagnosis and immediate therapeutic intervention by steroid were instrumental in helping our patient survive DAH [14,15]. Second, clinicians should be alert to the possibility that DAH can occur in patients taking methimazole.…”
Section: Discussionmentioning
confidence: 98%
“…DAH is a syndrome characterised by bleeding into alveolar spaces without inflammation or destruction of the alveolar structures, there by differing from the pulmonary capillaritis type by the lack of systemic vasculitis and connective tissue disorders within a spectrum ranging from asymptomatic radiographic abnormalities to severe life-threatening respiratory failure (1,2) .…”
Section: Discussionmentioning
confidence: 99%
“…DAH may occur in the context of various systemic disorders or may be present in isolation (2) . The presence of DAH after coronary artery bypass surgery is a rare complication.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, de Prost et al reported that the major etiologies of DAH were not immunerelated, such as cardiac dysfunction (8). Although vasculitis is considered to be the main etiology of DAH, the pathophysiology of bland DAH, especially that due to cardiac disorders, should be emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant diseases were evaluated according to BALF cytology. The diagnosis of acute exacerbation of interstitial pneumonia was made based on existing criteria (7), and clotting disorders were diagnosed according to a platelet count of <15,000/mL or prothrombin time-international normalized ratio of >1.5, based on a previous report (8). In addition, the diagnosis of drug-induced lung injury was established in cases with a compatible chronology of adverse events following exposure to known pneumotoxic drugs; this diagnosis required the exclusion of other causes.…”
Section: Definitions Of the Underlying Causes Of Dahmentioning
confidence: 99%